Immunomodulatory Activity of Xestospongia sp. Ethanolic Extract Towards Interferon-gamma (IFN- Î³) and Tumor Necrosis Factor-alpha (TNF-Î±) Levels in Wistar Male Rats - Fristiohady, Adryan; Jumadil; Wahyuni; Malaka, Muh. Hajrul; Harnita, Wa Ode; Sadarun, Baru; Yodha, Agung Wibawa Mahatva; Saripuddin; Purnama, La Ode Muhammad Julian; Sahidin, Idin (Jurnal Farmasi Galenika (Galenika Journal of Pharmacy) (e-Journal), 2020)
Xestospongia sp. is one of marine sponge belongs to demosponges class that mainly found in Southeast Sulawesi and the secondary metabolites contained in Xestospongia sp. suspected to have immunomodulatory activity. A previous study exhibited the immunomodulatory of Xestospongia sp. ethanolic extract (XEE) at dose of 300 and 400 mg/Kg BW by affecting the phagocytic activity of macrophages. Thus, this study aims to investigate the effect of XEE towards interferon-gamma (IFN-Î³) and tumor necrosis factor-alpha (TNF-Î±) at dose of 300 and 400 mg/Kg BW. Wistar male rats are divided into 4 groups (n=6) randomly and treated for 7 days orally each as follow: group I (XEE dose of 300 mg/KgBW); group II (XEE dose of 400 mg/KgBW); group III (0.5% NaCMC); and group IV (commercial phylantii extract). On day 8, animals were infected with Staphylococcus aureus and left for 1 hour. Animals were sacrificed and the blood was drawn by cardiac puncture (3 mL), followed by analyzed under ELISA Kit for IFN-Î³ and TNF-Î±. Collected data were analyzed statistically using SPSSÂ®. The IFN-Î³ levels obtained were 350.113; 392.970; 118.416; and 61.958 Ïg/mL, respectively and the TNF-Î± were 2808; 1308; 778; and 845.5 Ïg/mL, respectively. According to results obtained, both doses of XEE are affecting the IFN-Î³ and TNF-Î± levels (p<0.05) compared to group III as negative control, and group IV as positive control. As conclusion, XEE of both doses is increasing IFN-Î³ and TNF-Î± levels of animals that respond to phagocytic activity